DRHC synthesis for simultaneous tracking and formation of nonhomogeneous multi-agents with time-varying communication topology. (15th June 2017) - Wang, Peng; Feng, Xinxi; Li, Weihua; Yu, Wangsheng
The synthesis approach of distributed receding horizon control is studied for the simultaneous tracking and formation problem of nonhomogeneous multi-agents. Different from the existing works, the communication topology between multi-agents is allowed to be time-varying in this article, which meets miscellaneous conditions in practice. To accommodate the time-varying communication topology, we refresh at each sampling instant the individual cost function for each agent, according to the real-time neighbourhood. Moreover, to guarantee the exponential stability of the overall closed-loop system, we design an auxiliary constraint and impose it in the individual optimization problem. The recursive feasibility of the auxiliary constraint can be guaranteed by updating the formation weighting scalars in real time. By solving the individual optimization problem (with respect to the input, state and auxiliary constraints) at each sampling instant, each agent can obtain its optimal control input sequence. The implementation of the first control input among the sequence for each agent can steer the overall multi-agent system to cooperatively achieve the desired tracking and formation objective. The effectiveness and practicability of our results are demonstrated through the illustrative examples.